Preparation of the 2020-2024 Riau Provincial Government Bureaucratic Reform Planning - Trio Saputra; Eka Eka; Wasiah Sufi (LP2M Universitas Jember, 2021)
This article was written based on the activities of assisting the preparation of the road map for bureaucratic reform in the province of Riau. Assistance based on the problems observed in the 2015-2019 bureaucratic reform activities and FGD with the partners of the Regional Secretariat Organization Bureau of Riau province who were the target of community service. Assistance in the preparation of the Riau provincial government bureaucratic reform road map 2020-2024 was carried out with the aim of increasing and accelerating the implementation of bureaucratic reform in Riau province. It is important to prepare a bureaucratic reform document as a guide for all stakeholders in implementing the bureaucratic reform agenda. With the preparation of a bureaucratic reform road map, each Regional Apparatus Organization (OPD) knows and understands the implementation of bureaucratic reform.